Hepatitis B vaccination coverage rates among under-five children in India: a systematic review and meta-analysis protocol - Divyasree Bhat, K.; Sinha, Abhinav; Bhattacharya, Haimanti; Jayaraman, Yuvaraj; Bhattacharya, Debdutta; Pati, Sanghamitra (Frontiers in Pediatrics, 2025)
BackgroundHepatitis B virus (HBV) affects an estimated 1.5 million people globally each year, with nearly 296 million living with chronic infection, contributing significantly to cirrhosis, liver cancer, and premature mortality. Despite the availability of a highly effective vaccine, hepatitis B remains endemic in many low- and middle-income countries, including India, due to barriers in healthcare access and low vaccination uptake. While a timely birth dose prevents perinatal transmission, completion of the full vaccine schedule is essential to prevent horizontal transmission—a major mode of infection in India. India introduced the hepatitis B vaccine in select districts in 2002–2003 and scaled it nationally through the Universal Immunization Programme in 2011–2012.ObjectiveThis systematic review and meta-analysis aims to estimate the pooled coverage of hepatitis B vaccination among children under 5 years of age across different regions of India.Methods and analysisA comprehensive literature search will be conducted using PubMed, Embase, and CINAHL databases to identify studies published between 1 January 2000 and 30 May 2024. The search terms will include “Hepatitis B,” “vaccination coverage,” “children,” and “India,” combined using Boolean operators. Two independent reviewers will screen titles, abstracts, and full-text articles for eligibility. The AXIS tool will be used to assess the quality of cross-sectional studies. Pooled coverage rates will be estimated using a random-effects meta-analysis model. Heterogeneity will be assessed using the I2 statistic and Cochran's Q test. Publication bias will be evaluated through funnel plots and Egger's test. Sensitivity and subgroup analyses will be conducted to explore the robustness of results and sources of heterogeneity.